Peran Brand Community dalam Pembentukan Minat Beli Ulang Konsumen - Purba, Daniela Anggita Kristi (Jurnal Aplikasi Manajemen, 2015)
Repurchase intentions is an important factor in determining the existence of a business as well as indicating the success of a product that is offered by the company. Companies are trying to develop an effective marketing strategy such as building brand communities in order to create loyal customers. This research analyzes how brand community create customer repurchase intention. The result of the analysis shows that brand community can give a negative effect on repurchase intention. On the other hand, if a brand community is being managed properly, it will create loyal customers. Loyal customers will have repurchase intention because the experience that they had with the brand can create satisfaction and trust.